2008
DOI: 10.1016/j.bpc.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the overall kinetic parameters of enzyme inactivation using an isoconversional method

Abstract: Please cite this article as: D. Oancea, Alexandrina Stuparu, Madalina Nita, Mihaela Puiu, Adina Raducan, Estimation of the overall kinetic parameters of enzyme inactivation using an isoconversional method, Biophysical Chemistry (2008Chemistry ( ), doi: 10.1016Chemistry ( /j.bpc.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Oancea at al . have developed a new application of an isoconversional method for determining kinetic parameters of the thermal and operational inactivation of enzymes.…”
Section: Denaturation Of Proteinsmentioning
confidence: 99%
“…Oancea at al . have developed a new application of an isoconversional method for determining kinetic parameters of the thermal and operational inactivation of enzymes.…”
Section: Denaturation Of Proteinsmentioning
confidence: 99%
“…This method was previously used to detect the suicide inactivation of catalase at high substrate concentration, thermo-inactivation of catalase and urease. 25 For HRP, the reported inactivation rate constants was around 10 -3 s -1 for guaiacol and capsaicin 26 and 10 -2 s -1 for 2-aminophenol. 27 In the case of BB oxidation, the isoconversional times were calculated for two settled values of BB concentration, corresponding to an initial part of reaction when 15% of BB is decomposed and at moderate substrate conversion, when 50% of BB is decomposed.…”
Section: Testing the Operational Inactivation Of Hrpmentioning
confidence: 98%
“…24 The examination of extended progress curves (concentration of either substrate or product vs. time) performed at settled initial concentration of substrates and different initial enzyme concentration, allows the estimation of the overall inactivation constant using an isoconversional method. 25 The method involves the determination of the time values (t [ ] ( )…”
Section: Testing the Operational Inactivation Of Hrpmentioning
confidence: 99%
“…The activation energies of gel melting have been positive and decrease throughout the process, whereas the numerical values of the activation energy have been found to depend systematically on the conditions of preparation such as the time and/or the temperature of gelation and the concentration of the gelatin solution . An isoconversional method has been applied by Oancea et al to evaluate the kinetics of enzyme inactivation. It has been concluded that the method yields good estimates for the global inactivation constant.…”
Section: Kineticsmentioning
confidence: 99%